2004
DOI: 10.1038/sj.npp.1300534
|View full text |Cite
|
Sign up to set email alerts
|

Psychostimulants Induce Low-Frequency Oscillations in the Firing Activity of Dopamine Neurons

Abstract: The reinforcing properties of psychostimulants depend critically on their effects on dopamine (DA) neurons in the ventral tegmental area (VTA). Using in vivo single unit recording in rats and spectral analysis, this study presents evidence for a new, non-DA-mediated effect of psychostimulants on VTA DA neurons. Thus, as previously observed with D-amphetamine, all psychostimulants tested, including cocaine, methamphetamine, and methylphenidate, had two opposing effects on firing rate of DA neurons: a DA-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
92
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(102 citation statements)
references
References 33 publications
7
92
3
Order By: Relevance
“…Treatment with the DA antagonists used in our study should also prevent a slowly developing inhibition, which is presumably mediated via DA autoreceptors. In fact, instead of inhibition, cocaine increased the activity of presumed DA VTA neurons in anesthetized animals treated with raclopride, a selective D2 antagonist (Shi et al, 2004). In contrast to rapid, transient excitations produced by cocaine at low dose in our experiments, this increase was tonic and much weaker despite the much higher drug dose.…”
Section: Sensory Effects Of IV Cocaine On Different Subgroups Of Vta contrasting
confidence: 62%
See 1 more Smart Citation
“…Treatment with the DA antagonists used in our study should also prevent a slowly developing inhibition, which is presumably mediated via DA autoreceptors. In fact, instead of inhibition, cocaine increased the activity of presumed DA VTA neurons in anesthetized animals treated with raclopride, a selective D2 antagonist (Shi et al, 2004). In contrast to rapid, transient excitations produced by cocaine at low dose in our experiments, this increase was tonic and much weaker despite the much higher drug dose.…”
Section: Sensory Effects Of IV Cocaine On Different Subgroups Of Vta contrasting
confidence: 62%
“…Cocaine-induced excitations of LS VTA neurons seen in this study appear to contrast to mainly inhibitory responses of presumed DA neurons to iv cocaine reported in the SNc and VTA in anesthetized animals (Einhorn et al, 1988;Hinerth et al, 2000;Pitts and Marwah, 1987;Shi et al, 2004). However, this latter effect was much slower (latencies 20-40 s), much more prolonged (10-20 min), relatively weak both on SNc and VTA neurons (ED 50 8.8 and 1.2 mg/ kg, respectively; Hinerth et al, 2000), and blocked by D2 antagonists (Zhou et al, 2006), suggesting its central pharmacological determination.…”
Section: Sensory Effects Of IV Cocaine On Different Subgroups Of Vta contrasting
confidence: 47%
“…This non-DA-mediated effect, expressed as an increase in both firing rate and a slow oscillation (SO) in firing pattern, is most evident when the DA-mediated feedback mechanisms are blocked. Results further show that the excitatory effect of D-amphetamine depends on forebrain inputs to DA neurons and requires activation of adrenergic a1 receptors (Shi et al, 2000b(Shi et al, , 2004.…”
Section: Introductionmentioning
confidence: 75%
“…The resulting increase in extracellular DA, in turn, activates various feedback mechanisms, leading to an inhibition of DA cell firing and thus a decrease in impulse-dependent DA release (Bunney et al, 1973;Groves et al, 1975;Bunney and Aghajanian, 1978;Wang, 1981;Shi et al, 2000a). We have recently shown that D-amphetamine also has an excitatory influence on DA neurons through a non-DA mechanism (Shi et al, 2000b(Shi et al, , 2004. This non-DA-mediated effect, expressed as an increase in both firing rate and a slow oscillation (SO) in firing pattern, is most evident when the DA-mediated feedback mechanisms are blocked.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation